Public Opinion on Immigration: Has the Recession Changed Minds? - Timothy J. Hatton (Institute for the Study of Labor (IZA), 2014)
It is widely believed that the current recession has soured public attitudes towards immigration. But most existing studies are cross sectional and can shed little light on the economy-wide forces that shift public opinion on immigration. In this paper I use the six rounds of the European Social Survey (2002-2012) to test the effects of economic shocks on immigration opinion for 20 countries. The recession that began in 2008 provides a useful test because its severity varied so widely across Europe. For Europe as a whole the shifts in average opinion have been remarkably mild. But trends in opinion have varied across countries, especially in the responses to a question on whether immigrants are good or bad for the economy. At the country level, pro-immigration opinion is negatively related to the share of immigrants in the population and to the share social benefits in GDP, but only weakly to unemployment. These effects differ somewhat across responses to different questions relating to immigration policy and to the desirability of immigrants. The recession also influenced other attitudes and traits that are sometimes linked to opinion on immigration.
Keywords: D72; F22; J61; 330; public opinion; immigration attitudes; immigration policy